ANALISIS PENERAPAN GOOD CORPORATE GOVERNANCE (GCG) DALAM HUBUNGANNYA DENGAN KINERJA KEUANGAN PADA PT. BANK RAKYAT INDONESIA SYARIAH - Shar, Aan; Novrianda, Herry (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2016)
The objective of this research is know good corporate governance (GCG) implementation in relation with financial performance PT. Bank Rakyat Indonesia Syariah. This research is a descriptive research with data collection methods used sekuder data from annual report and good corporate governance report and primary data through questionnaire distribution. The data analysis is technique uses return on assets (ROA) and mean method with the frequency distribution table. The results that, the implementation of good corporate governance in relation to financial performance PT. Bank Rakyat Indonesia Syariah has been running well. Furthermore, the application of the principles of transparency, accountability, responsibility, independency and fairness have been effective with the average value of each statement of 3.69 (good), 3.89 (good), 3.76 (good), 3.67 (good), 3.85 (good). And the financial performance of PT. Bank Rakyat Indonesia Syariah in the period 2012-1216 in healthy category with average return on assets (ROA) that is equal to 0.76%.Keywords: Good Corporate Governance, Financial Performance, Transparency, Accountability, Responsibility, Independency, Fairness